Digital frequency synthesis demystified DDS and fractional-N PLLs - Goldberg, Bar-Giora
In-depth coverage of modern digital implementations of frequency synthesis architectures. Numerous design examples drawn from actual engineering projects. The accompanying CD includes digital frequency synthesis design tools and an electronic version of the book. Digital frequency synthesis is used in modern wireless and communications technologies such as radar, cellular telephony, satellite communications, electronic imaging, and spectroscopy. This is book is a comprehensive overview of digital frequency synthesis theory and applications, with a particular emphasis on the latest approa.